Repair Replication of HeLa Cell Deoxyribonucleic Acid in Cells Infected with Newcastle Disease Virus or Mengovirus or Treated with Puromycin - Hand, Roger (1971)
We examined repair replication of HeLa cell deoxyribonucleic acid (DNA) in cells infected with mengovirus or Newcastle disease virus or treated with puromycin. Cellular DNA was damaged by ultraviolet light and then pulse-labeled with (3)H-thymidine. Autoradiographic analysis of non-S-phase DNA synthesis (repair replication) showed that there was no inhibition of this process at a time when overall cellular DNA synthesis was severely inhibited by either virus infection or puromycin treatment.